Competence approach to the formation of future teachers’ physical competence - Sokolyuk, O. V. (Problems of Engineer-Pedagogical Education, 2018)
The analysis of psychological and pedagogical sources carried out by the author shows the relevance of the chosen topic in the article. Based on the analysis of scientific pedagogical literature and her own experience of teaching in a higher education pedagogical establishment, the author proposes to use competence-based approach to improve the quality of physical education and to solve problems of professional training of future teachers for the acquisition of physical competence. The author proves that the competence approach provides a different role of a student in the educational process, it is based on work with information, modeling, reflection; a future specialist must be able not just to reproduce information, and to think independently and be ready for real life situations. It is clarified that competence is an integrated combination of personal qualities, knowledge, and skills of their practical use for solving various professional tasks; physical competence is prescribed by the standard requirements to results of the educational training of bachelor's in the discipline "Physical culture" (knowledge, skills and ways of activity), and physical competence is a specific ability to implement sports activities, taking into account the professional knowledge, skills, personal qualities for effective use in a particular subject area.